Peningkatan Imunitas Selama Masa Pandemik Covid-19 - Aida Yulia; Helda Helda; Rini Vovriyenti; Leni Tri Wahyuni; Wuri Komalasari (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
The present world-wide pandemic may have adverse effects on health, economics, social, and political life as well as on all age stages. The covid-19 treatment efforts have been made by both governments and private governments in the form of vaccinating, improving healthy life behaviour and getting used to health protocols. Teenagers are one of the risky groups either carrier or covid-19 patients, it's because of those with the stage age groups in search of identity and socialize with peer groups. This situation takes youth as a very potential group to transmit to those around them with activities they are experiencing. The purpose of this activity is to give knowledge and technical guidance to students in MAN 1 Padang. As for the methods used in the activity through direct instrumentation and training of materials and evaluation at the time of the operation involving presentations, discussions, demonstration and re-demonstration of the washing of hands and the wearing of masks. The results of this activity are found to be almost entirely to all teenagers participating in the activity can relate to covid-19 and the attempts made to increase immunity in the pandemic of covid-19. It is hoped that youth can change into a creative, innovative young agent who offers input, ideas and suggestions to help promote clean and healthy, by continuing health protocol in the community in a community setting.